Schooling and labour market impacts of Bolivia's Bono Juancito Pinto - Carla Canelas; Miguel Ni\~no-Zarazúa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
In 2006, the Bolivian government introduced a large-scale cash transfer programme, Bono Juancito Pinto (BJP). Exploiting the exogenous variation of the programme expansion, this paper examines the impact of BJP on schooling and child labour. The analysis suggests that the transfer increases the likelihood of school enrolment but has no sizeable effect on the incidence of child labour. The results are in line with theoretical models that predict that if leisure and schooling decisions are substitutes, a school incentive will have either positive or neutral effects on child labour. Our findings support previous evidence that schooling and work decisions are not perfect substitutes among children.
Keywords: I25; I38; J13; J22; N36; 330; Bolivia; child labour; conditional cash transfers; schooling